3D digital image microscope system-assisted vasovasostomy and vasoepididymostomy in rats - Peng Li; Na-Chuan Liu; Er-Lei Zhi; Chen-Cheng Yao; Zhi-Liang Zhao; Zhi-Yong Yu; Qi-Meng Li; Yu-Hua Huang; Jie-Chang Ju; Wen-Bin Huang; Husanjan Rozi; Zhi-Yong Ji; et al. (Asian Journal of Andrology, 2021)
Optimal vision and ergonomics are essential factors contributing to the achievement of good results during microsurgery. The three-dimensional (3D) digital image microscope system with a better 3D depth of field can release strain on the surgeon's neck and back, which can improve outcomes in microsurgery. We report a randomized prospective study of vasoepididymostomy and vasovasostomy using a 3D digital image microscope system (3D-DIM) in rats. A total of 16 adult male rats were randomly divided into two groups of 8 each: the standard operating microscope (SOM) group and the 3D-DIM group. The outcomes measured included the operative time, real-time postoperative mechanical patency, and anastomosis leakage. Furthermore, a user-friendly microscope score was designed to evaluate the ergonomic design and equipment characteristics of the microscope. There were no differences in operative time between the two groups. The real-time postoperative mechanical patency rates were 100.0% for both groups. The percentage of vasoepididymostomy anastomosis leakage was 16.7% in the SOM group and 25.0% in the 3D-DIM group; however, no vasovasostomy anastomosis leakage was found in either group. In terms of the ergonomic design, the 3D-DIM group obtained better scores based on the surgeon's feelings; in terms of the equipment characteristics, the 3D-DIM group had lower scores for clarity and higher scores for flexibility and adaptivity. Based on our randomized prospective study in a rat model, we believe that the 3D-DIM can improve surgeon comfort without compromising outcomes in male infertility reconstructive microsurgery, so the 3D-DIM might be widely used in the future.